Awareness of palliative care among general nursing and midwifery nurses in nursing institutes of Assam by palliative care quiz for nursing tool - Barbhuiya, Maruf H.; Deka, Arun; Mazumdar, Dimpy; Das, Shantana; Upamanyu, Nivedita (International Journal of Research in Medical Sciences, 2023)
Background: Amidst the increasing prevalence of non-communicable diseases and an aging populace, the demand for palliative care (PC) is escalating. Nurses, as primary caregivers in healthcare, play a pivotal role in providing PC. Assessing their current knowledge levels is crucial for devising targeted strategies to address deficiencies and enhance the quality of palliative care delivery. Methods: A survey-based study was done in 10 nursing institute across Assam which were selected randomly after obtaining ethical committee clearance from the institute. A total of 239 participants filled the questionnaires. The questionnaire contained 2 parts; sociodemographic characteristics and palliative care quiz for nursing (PCQN) which is a validated questionnaire consisting of 20 items that measures nurses’ knowledge of palliative care. The responses to the statements in the PCQN will be: true, false, and I don’t know. A correct answer was scored 1 while an incorrect or I don’t know was scored 0, giving a maximum score of 20. A score equal to or less than ≤10 on PCQN was considered inadequate knowledge while a score >10 was considered adequate knowledge. Results: 55% participants had adequate knowledge about palliative care and the mean PCQN score was 12.59±5.8. P value was found to be significant which means those with prior knowledge of palliative care had good score. Conclusions: This study underscores a positive shift in palliative care awareness among nursing students, attributed to curriculum integration. However, targeted improvements are needed, especially in psychosocial and spiritual aspects, to enhance patient care and attitudes.